Photographic Researcher: New Zealand - Browning, Kathy (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
In 2018, Kathy Browning spent 32 days in New Zealand on the South and North Islands taking 15,240 digital photographs. This was followed by a year of close study and editing of her digital images as ways to share photographic stories of this artistic research. How can one represent the deep feelings experienced when one is taking the photograph? The visual narrative that emerged from this series is similar to grounded theory used for her academic research. Thus, instead of travelling to the islands with a set of preconceived ideas, a research protocol or a list of ‘what-to-photograph’, the author let this field of study, the landscape of New Zealand, guide the photographic act. The article also addresses how after decades of teaching and showing art in exhibitions, the media of photography inspired and informed her teaching of visual arts education.